Effects of digital games training on hormonal responses and brain plasticity (Research, Society and Development, 2023)
Digital games are a ubiquitous part of almost all children’s and adolescents’ lives. At the same time gaming industry is ready to unlock new levels of growth in the coming years (Granik et al., 2014). A growing number of studies have already focused on the beneficial effects of digital games on various aspects of cognition and health. However, less emphasis has been given to the physiological biomarkers that operate in the background and cause various modifications in players’ mental and emotional states as well as their ability to be aware and take control over their decisions and actions. Hormones and neurotransmitters regulate homeostasis and determine to a significant extent humans’ health, state of mind, and self-awareness abilities. Neuroplasticity is now recognized as a crucial factor in acquiring new skills and abilities. The present study aims to investigate the impact of digital game-playing on hormone responses and neuroplasticity phenomena. To this objective, we conducted a literature review presenting the most representative experimental studies. The results showed that digital games have significant effects on hormone responses and neuroplasticity phenomena. Finally, we discuss the factors that may contribute to alterations in digital game players’ homeostasis. The findings of this review aim to contribute to the discussion regarding the design of targeted, novel game-based intervention tools that have the potential to improve homeostasis, drive positive neuroplasticity, accelerate metacognitive learning, and thereby promote mental and emotional well-being for both typical populations, but most importantly, for people with learning disabilities, mental and other disorders.